Sistem Pakar Memilih Tipe Belajar Anak Retardasi Mental Menggunakan Metode Case Based Reasoning - Dasril Aldo; Khairunnisa Samosir; Yeyi Gusla Nengsih (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2021)
Mental retardation is an intellectual disability characterized by intelligence being below average. People who are mentally retarded can learn new abilities, but the pace of learning is very slow. There are problems that often occur in the detection that children have mental retardation, especially by parents due to the lack of knowledge of the parents about this, resulting in the mistake of choosing the right type of learning for children. If this is allowed to continue, it will result in the child's mental condition getting worse. Due to these problems, a solution is offered in the form of an expert system application with the Case Based Reasoning (CBR) method, this method will match the symptom data of the old disease with the symptom data consulted by the user so that the similarity number of each type of mental retardation will be produced. The final result of this study is the percentage value of similarity along with recommendations in the form of suggestions and solutions that will be carried out by parents in providing independent education to children with mental retardation. The results obtained were in the form of mental retardation with a percentage of 0%, disabled with a percentage of 82.35%, with disabilities with a percentage of 0%.